Evaluation of the analytical and clinical characteristics of the Siemens IMMULITE®2000 TSI method for determining thyrotropin receptor antibodies: Method for determining thyrotropin receptor antibodies - Milinković, Neda; Sarić, Marija; Ružanović, Ana; Žarković, Miloš; Ćirić, Jasmina; Perović Blagojević, Iva; Mastilović, Ana Marija; Ignjatović, Svetlana; Nedeljković Beleslin, Biljana (Journal of Medical Biochemistry, 2025)
Background: Despite commercially improved, standardized routine methods used in medical laboratories, precision laboratory medicine lacks harmonization of results to make the laboratory result useful for its intended purpose. Furthermore, in order to obtain reliable laboratory results and precise diagnoses, it is important and recommended that each laboratory confirms the analytical and clinical characteristics of the method used. The aim of this study was to evaluate the analytical and clinical performance of the IMMULITE®2000 TSI bridge immunoassay for the determination of autoreactive thyroid stimulating hormone receptor antibodies (ТSH-R-Ab). Methods: A total of 86 patients with clinically present Graves’ orbitopathy and 23 healthy volunteers as a control group were included in the study. The total TSH-R-Ab concentration was determined using an ECLIA (Elecsys Anti-TSHR Immunoassay Roche Diagnostics, GmbH, Mannheim, Germany) on the Cobas e411 analyzer (Roche, Diagnostics, GmbH). The TSH-R-Ab concentration was measured using a CLIA method (IMMULITE TSI 2000, Siemens Healthcare Diagnostics, UK). The inaccuracy of the method was investigated using two levels of commercial control samples (low and high analyte concentration). Results: The results obtained meet the general minimum requirements for the analytical performance of laboratory methods (CV <5%). The overall laboratory inaccuracy was acceptable according to FDA guidelines (CV<20%). The results showed a statistically significant correlation between the analyzed methods (r=0.9041, p ˂ 0.0001), but with a relative bias of 24.5%. The best ratio of sensitivity and specificity determined by the ROC analysis (93.3 % and 100 % respectively) was obtained for a cut-off value of 0.1215 IU/L, which is significantly lower compared to the cut-off value specified by the manufacturer (0.55 IU/L). Conclusion: The IMMULITE 2000 TSI bridge immunoassay for TSH-R-Ab quantification confirmed an adequate level of precision, which is essential for routine use. However, further studies are required to evaluate its analytical specificity.